Assisted Reproductive Technologies: A New Player in the Foetal Programming of Childhood and Adult Diseases? - Gavino Faa; Mirko Manchia; Vassilios Fanos (MDPI AG, 2024)
Assisted reproductive technology (ART) is an emerging field in medicine that incorporates complex procedures and has profound ethical, moral, social, religious, and economic implications not just for the individuals who have access to this method but also for society. In this narrative review, we summarise multiple aspects of ART procedures and the possible consequences on the mother and newborn. Moreover, we provide an overview of the possible long-term consequences of ART procedures on the health of newborns, although longitudinal evidence is particularly scant. Users should be informed that ART procedures are not risk-free to prepare them for the possible negative outcomes that may occur in the perinatal period or even in childhood and adulthood. Indeed, risk estimates point to increased liability for major nonchromosomal birth defects; cardiovascular, musculoskeletal, and urogenital (in male newborns) defects; and any other birth defects. Less certainty is present for the risk of neuropsychiatric sequelae in children conceived through ART. Thus, its application should be accompanied by adequate counselling and psychological support, possibly integrated into specific multidisciplinary clinical programmes.